Dampak Kekerasan Seksual Terhadap Konstruksi Makna Pernikahan pada Perempuan Dewasa - Naila Rosdiana Zulfany; Mulya Virgonita IW; Margaretha Maria Shinta Pratiwi (EduInovasi: Journal of Basic Educational Studies, 2025)
Sexual violence against women not only impacts physical and mental health but also fundamentally alters how they understand and construct meaning around the institution of marriage. This study aims to analyze the impact of sexual violence on marriage meaning construction among adult women through a systematic literature review method. Literature search was conducted through PsycINFO, PubMed, Scopus, Web of Science, and JSTOR databases with inclusion criteria of articles published in 2010-2024, focusing on adult women survivors of sexual violence, and relevant to marriage meaning construction. Results reveal dramatic transformation in marriage meaning construction, where the concept of marriage as a "safe haven" transforms into a source of anxiety and uncertainty. Women survivors experience expectation changes from optimistic to realistic or pessimistic, accompanied by profound fears of physical intimacy, loss of control, and potential re-traumatization. Intimacy and trust aspects experience the most complex impacts, creating difficulties in forming deep emotional connections. Nevertheless, women survivors demonstrate adaptive capacity through constructive coping strategies such as gradual communication with partners and seeking professional help. The meaning reconstruction process is influenced by internal factors (resilience, belief systems) and external factors (social support, access to mental health services). This research emphasizes the need for developing trauma-informed therapeutic interventions and holistic psychosocial support programs to help women survivors build healthy and meaningful marital relationships.